1993
DOI: 10.1063/1.465640
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the role of dipoles on the density-of-states function of disordered molecular solids

Abstract: The effect of permanent dipoles on the density-of-states (DOS) function of an array of hopping sites is examined by summing the contributions of individual dipoles to the total potential at a given site. For relative dipolar site concentrations ≳0.1, the DOS function is of Gaussian shape. At lower concentrations, it approaches a Lorentzian. Good agreement with literature data on the dipolar contribution to the DOS function for hole transport in molecularly doped polymers and molecular glasses differing with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
180
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(186 citation statements)
references
References 26 publications
6
180
0
Order By: Relevance
“…͑5͒ for a doped polymer containing a strong dipolar additive in addition to a polar charge transport agent. The data are more consistent with the linear dependence on concentration, n ϭ1, proposed by Young 35 and Dunlap, Parris, and Kenkre, 38 while the superlinear dependence, 2nϭ4/3, of Dieckman, Bässler, and Borsenberger 36 and Hirao and Nishizawa 37 would be too strong. The NAS chromophores have a larger effect on the energy width despite having a smaller dipole moment ͑6.7 D͒ than EHDNPB ͑7.6 D͒, but EHDNPB is much larger because of its alkyl tail ͓see Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…͑5͒ for a doped polymer containing a strong dipolar additive in addition to a polar charge transport agent. The data are more consistent with the linear dependence on concentration, n ϭ1, proposed by Young 35 and Dunlap, Parris, and Kenkre, 38 while the superlinear dependence, 2nϭ4/3, of Dieckman, Bässler, and Borsenberger 36 and Hirao and Nishizawa 37 would be too strong. The NAS chromophores have a larger effect on the energy width despite having a smaller dipole moment ͑6.7 D͒ than EHDNPB ͑7.6 D͒, but EHDNPB is much larger because of its alkyl tail ͓see Fig.…”
Section: Discussionsupporting
confidence: 84%
“…35,36,38 These are the first results showing the dipolar disorder effects due to independent dopants ͑NAS and EHD-NPB͒ and the transport agent study reveals that the proper choice of transport agents is important in achieving high mobilities in MDPs that contain other strong polar species.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…14,15 Here we show that the presence of large molecular dipole moments can be beneficial rather than disadvantageous for promoting charge hopping. Electrostatic attraction between the large fixed internal dipoles in these molecules leads to formation of centrosymmetric dimers with cofacial π-π antiparallel alignment along the long molecular axis.…”
mentioning
confidence: 70%
“…[5,6] Via the calculation of local electric fields for a number of different hopping sites, it could be shown that the disorder parameter σ depends on the polarity and the polarizability of the transport material. [7] This result is supported by experiments demonstrating that polar side chains in polymeric semiconductors have a detrimental effect on charge carrier mobilities by increasing the disorder in the DOS. [2] A more profound understanding of these and other parameters influencing the disorder is needed to rationally design materials with favorable transport properties because small energetic disorder is decisive for efficient exciton and charge transport in molecular semiconducting thin films of optoelectronic devices.…”
mentioning
confidence: 81%